2016
DOI: 10.1109/lpt.2016.2578643
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processable MoO<italic>x</italic>for Efficient Light-Emitting Diodes Based on Giant Quantum Dots

Abstract: We report efficient quantum dot light-emitting diodes (QLEDs) using sizable 13-nm green-emission quantum dots (QDs) as the emissive layer and solution-processable MoOx as the hole injection layer (HIL). The MoOx HIL was prepared by the decomposition of a solution of ammonium molybdate tetrahydrate at 80 C under ambient conditions, further spin-coated onto an ITO substrate to facilitate hole injection. Compared to the reference sample with a polymeric hole injection material poly(3,4-ethylenedioxythiophene):po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Nguyen et al report the QLEDs with solution‐processed inorganic p‐type semiconductor NiO x as the HIL, showing a current efficiency of 2.54 cd A −1 . Vu et al report the preparation of solution‐processed MoO x film instead of PEDOT:PSS as the anode interfacial buffer layer, and the MoO x film shows better transparency, and smoother surface morphology. Recently, Cao et al report highly efficient QLEDs using NiO x HIL.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al report the QLEDs with solution‐processed inorganic p‐type semiconductor NiO x as the HIL, showing a current efficiency of 2.54 cd A −1 . Vu et al report the preparation of solution‐processed MoO x film instead of PEDOT:PSS as the anode interfacial buffer layer, and the MoO x film shows better transparency, and smoother surface morphology. Recently, Cao et al report highly efficient QLEDs using NiO x HIL.…”
Section: Introductionmentioning
confidence: 99%
“…For samples from F3 to F5, the PL peak blue-shifted to the original location of QD film (528 nm) with Al 2 O 3 insertion, and the emission intensity and lifetime also showed an obvious increase, which confirmed the positive effect on passivating the surface of the NiO x layer and suppressing the emission quenching induced by NiO x through the introduction of the Al 2 O 3 layer, and such results were consistent with the previously reported findings. It is reported that the sMoO x film showed a higher work function of 5.6 eV, better transparency, and smoother surface morphology, providing the QLEDs with good Ohmic contact and small charge transfer resistance (He et al, 2013;Vu et al, 2016). The device structure was further optimized by using sMoO x as HIL to expect an even better device performance.…”
Section: Resultsmentioning
confidence: 99%
“…The NiO x precursor was prepared by a modified method (Mashford et al, 2010); the mixture of nickel acetate tetrahydrate [Ni(OAc) 2 ·4H 2 O; purchased from Aldrich] and equimolar quantity of monoethanolamine (MEA; purchased from Aldrich) in ethanol was heated at 60 • C for 2 h and stirred overnight. 0.1 M MoO x solutions were synthesized by a thermal decomposition method using ammonium heptamolybdate [(NH 4 ) 6 Mo 7 O 24 ·4H 2 O] as a precursor (Murase and Yang, 2012;Vu et al, 2016). The ZnO NPs were prepared by slowly mixing 0.1 M zinc acetate in dimethyl sulfoxide (DMSO) and 0.3 M tetramethylammonium hydroxide (TMAH) in ethanol together for 1 h, and the ZnO particles were precipitated by adding hexane/ethanol to the solution.…”
Section: Preparation Of Green Quantum Dots and Metal Oxide Solutionmentioning
confidence: 99%
“…On the other hand, to improve the hole injection for better charge balance, the PEDOT:PSS was replaced by the sol-gel-derived NiO x film in MAPbBr PeLEDs and solar cells [16,17]. Similar p-type or n-type metal oxides have been widely used in OLEDs and quantum dot LEDs (QLEDs) and gained great improvement of device performance [18][19][20][21]. In this article, to modify the surface morphology and optical characteristics of sol-gel derived CsPbBr 3 emissive layer (EML), the precursors, CsPbBr 3 and CsBr, were blended with polyethylene oxide (PEO), 1,3,5-tris (N-phenylbenzimiazole-2-yl) benzene, and bis(3,5-difluoro-2-(2-pyridyl)phenyl-(2-carboxypyridyl) iridium III (FIrpic) at certain ratio in dimethyl sulphoxide (DMSO).…”
Section: Introductionmentioning
confidence: 99%